Analisis Program Ekstrakurikuler Kepramukaan Dalam Membangun Disiplin Siswa Belajar PAI - Hairunnisa (AL-IBNOR, 2024)
Character education is an important thing in supporting the development of students among these efforts including through the scouting extracurricular program to build student discipline learn to pai, in scouting there are values and norms that can be applied to scout activities. This research method uses qualitative methods which are library research (library research) referring to and examining scientific journals, reference books, literature, encyclopedias, scientific research, as well as reliable sources that are relevant as research objects, this type of qualitative research is a method that produces information in the form of data and descriptive notes in research texts. The results, Scouting extracurriculars play a very important role in building student discipline in learning PAI and other learning where in extracurricular activities there are very many positive values that are instilled and directed to students, it only remains for educators and students to apply them in everyday life.